Effects of Prereactivation Propranolol on Cocaine Craving Elicited by Imagery Script/Cue Sets in Opioid-dependent Polydrug Users: A Randomized Study. Issue 6 (November 2015) - Jobes, Michelle L.; Aharonovich, Efrat; Epstein, David H.; Phillips, Karran A.; Reamer, David; Anderson, Micheline; Preston, Kenzie L.
Abstract : Objectives: Relapse to drug misuse may follow exposure to drug cues that elicit craving. The learned associations, or "emotional memories, " that underlie responses to cues may be attenuated or erased by the β-adrenergic antagonist propranolol during a "reconsolidation window" shortly after the memories are reactivated by cues. Methods: We evaluated the effects of propranolol on cue-induced drug cravings in healthy opioid-dependent individuals who used cocaine while receiving methadone maintenance (n = 33). Participants were asked to recall specific cocaine use and neutral events in an interview; these events were used to develop personalized auditory script/cue sets. Approximately 1 week later, propranolol (40 mg) or placebo (random assignment, double blind) was administered orally before presentation of the script/cue sets; the presentation of the script/cue sets were tested 1 week and 5 weeks after the propranolol/placebo session. Ongoing drug use was monitored via urine screens and self-report in twice-weekly visits. Results: Cue reactivity, as assessed by craving scales and physiological responses, was unexpectedly greater in the propranolol group than in the placebo group. This counterhypothesized group difference was present acutely during propranolol administration and seemed to persist (without reaching statistical significance) during the subsequent test sessions. Conclusions: : Our results do not support the use of propranolol for cue-induced cocaine craving in opioid-maintained patients.